Possible Roles of Specific Amino Acids in β-Tubulin Isotypes in the Growth and Maintenance of Neurons: Novel Insights From Cephalopod Mollusks - Ludueña, Richard F. (Frontiers in Molecular Neuroscience, 2022)
Microtubules, are formed of the protein tubulin, which is a heterodimer of α- and β-tubulin subunits. Both α- and β-tubulin exist as numerous isotypes, differing in amino acid sequence and tissue distribution. Among the vertebrate β isotypes, βIII has a very narrow distribution, being found primarily in neurons and in advanced cancers. The places in the amino acid sequence where βIII differs from the other β isotypes are highly conserved in evolution. βIII appears to be highly resistant to reactive oxygen species and it forms highly dynamic microtubules. The first property would be very useful in neurons, which have high concentrations of free radicals, and the high dynamicity would aid neurite outgrowth. The same properties make βIII useful in cancers. Examination of the amino acid sequences indicates a cysteine cluster at positions 124–129 in βIII (CXXCXC). This occurs in all βIII isotypes but not in βI, βII, or βIV. βIII also lacks the easily oxidized C239. Both features could play roles in free radical resistance. Many aggressive tumors over-express βIII. However, a recent study of breast cancer patients showed that many of them mutated their βI, βII, and βIV at particular places to change the residues to those found at the corresponding sites in βIII; these are all sites that are highly conserved in vertebrate βIII. It is possible that these residues are important, not only in the resistance to free radicals, but also in the high dynamicity of βIII. The cephalopod mollusks are well known to be highly intelligent and can remodel their own brains. Interestingly, several cephalopods contain the cysteine cluster as well as up to 7 of the 17 residues that are highly conserved in vertebrate βIII, but are not found in βI, βII, or βIV. In short, it is possible that we are looking at a case of convergent evolution, that a βIII-like isotype may be required for neuronal growth and function and that a structure-function study of the particular residues conserved between vertebrate βIII and cephalopod tubulin isotypes could greatly increase our understanding of the role of the various tubulin isotypes in neuronal growth and function and could aid in the development of novel anti-tumor drugs.